Decarbonising Australia's National Electricity Market and the role of firm, low-carbon technologies. (1st November 2022) - Davis, Dominic; Brear, Michael J.
Abstract: Many of the world's electricity systems are decarbonising, driven in most cases by the deployment of variable renewable energy technologies. This paper studies such systems using generation expansion planning in the form of a linear program to determine and understand least-cost pathways to deep decarbonisation of existing wholesale electricity markets over a 30-year horizon. This work extends previous generation expansion modelling with several, additional options that now enable the substitution of woody biomass for coal and biomethane for natural gas, the retrofit of carbon capture and storage to existing and new build fossil plant, and different constraints on variable renewable energy that differentiate between renewable resource adequacy, system security and economic performance. The most recent, independent, and authoritative technical and financial input data are also used. In all decarbonisation pathways studied, emission reductions are primarily driven by the replacement of the existing coal fleet with utility-scale solar photovoltaic and wind generation. Nonetheless, systematic application of these additional options gives rise to a wide range of different technologies for 'firming' renewable-rich, decarbonised systems, with batteries, pumped hydroelectric energy storage, fossil plant with co-fired biomass and biomethane, carbon capture and storage and nuclear small modular reactors all playing significant roles in different cases. This range of observed pathways is thought to have several implications for system planning, with variable renewable energy tending to be economically competitive up to an imposed technical limit, but with that limit being uncertain and therefore requiring continuous re-evaluation as our understanding evolves. The results of an extensive range of sensitivity studies also suggest that deep decarbonisation is achievable without large increases in costs for consumers, that we should embrace the optionality and competition between different technologies, and that stakeholders have significant choice about non-cost related impacts and preferences, which are manifold. Highlights: Generation expansion demonstrates diverse pathways of power system decarbonisation. ∼90% abatement projected to be achieved via renewables competing solely on cost. Constraints on VRG integration impact prospects of firm-low carbon technologies. Additional costs of decarbonisation are relatively insensitive to technology mix. We should embrace optionality and competition between different technologies.